4-Chloro-N-(2,3-dimethylphenyl)benzenesulfonamide - K. Shakuntala; Sabine Foro; B. Thimme Gowda (Acta Crystallographica Section E, 2011)
In the title compound, C14H14ClNO2S, the two aromatic rings are tilted relative to each other by 34.7 (1)°. In the crystal, the molecules form zigzag chains along the c axis via intermolecular N—H...O hydrogen bonds.